Amantadine as a therapeutic option for neuropathic pain in dogs with degenerative lumbosacral stenosis - Chiara Caterino; Giovanni Della Valle; Federica Aragosa; Stefano Cavalli; Francesco Lamagna; Gerardo Fatone (BMC Veterinary Research)
Abstract Background Degenerative lumbosacral stenosis is a multifactorial condition with no consensus on optimal therapeutic management. In mildly affected dogs, treatment often includes analgesics and non-steroidal anti-inflammatory drugs, which may be insufficient for effective pain control. This study aimed to evaluate the efficacy of amantadine in managing chronic neuropathic pain associated with this pathology in dogs, using ground reaction forces (GRFs) analysis, including Peak Vertical Force (PVF), Vertical Impulse (VI), and stance time (ST), and to evaluate whether the co-administration of amantadine improves the efficacy of meloxicam in patients who have shown a refractory response to meloxicam alone. Methods Client-owned dogs (≥ 12 months old, ≥ 20 kg) with a confirmed diagnosis of degenerative lumbosacral stenosis were enrolled in a randomized trial. Subjects were assigned to two treatment groups: Group A received meloxicam (0.2 mg/kg PO SID loading dose, followed by 0.1 mg/kg SID for 6 days) plus amantadine (3 mg/kg PO SID for 21 days); Group B received amantadine alone (3 mg/kg PO BID for 21 days). Gait analysis was performed using a force platform at baseline (T0), after 7 days (T1), and after 21 days (T2). Results Twenty dogs met the inclusion criteria and completed the study. At enrollment, the two groups (10 animals each) were homogeneous. After 21 days, both groups showed significant increases in PVF%BW (p < 0.0001) and VI%BW (p = 0.0064 in Group A; p = 0.0023 in Group B). For VI%BW, Group A demonstrated a significant improvement between T0 and T1 (p = 0.0120), and T0 and T2 (p = 0.0083), but not between T1 and T2 (p = 0.4040). Group B showed significant increases between T0 and T2 (p = 0.0012), and T1 and T2 (p = 0.0034), but not between T0 and T1 (p = 0.7788). Regarding PVF%BW, both groups exhibited significant differences across all time points, showing progressive improvement over time. Conclusion The results suggest that amantadine, either alone or in combination with meloxicam, improves GRFs in dogs with degenerative lumbosacral stenosis and, may be a valuable component of its multimodal therapy, though additional research is necessary to validate these findings.